2020
DOI: 10.3390/ani10040638
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Occurrence and Parasite Management in Swedish Horses Presenting with Gastrointestinal Disease—A Case–Control Study

Abstract: Simple Summary: Abdominal pain, colic, is a common clinical sign in horses, sometimes reflecting life-threatening disease. One cause of colic is parasitic infection of the gut. Various drugs, anthelmintics, can be used to reduce or eliminate such parasites. However, frequent use has led to problems of drug resistance, whereby many countries now allow anthelmintics to be used on a prescription-only basis. In Sweden, this has led to a concern that parasitic-related colic in horses is increasing. This study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…Noteworthy, neither our data nor that of the latter Swedish study obtained any statistical association between colic and S. vulgaris positivity. This is in agreement with previous investigations on the occurrence of S. vulgaris [ 37 ] and also cyathostomins [ 38 , 39 ] in colic versus control horses. However, there are some publications describing the opposite, such as S. vulgaris -associated colic due to non-strangulating intestinal infarction [ 3 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Noteworthy, neither our data nor that of the latter Swedish study obtained any statistical association between colic and S. vulgaris positivity. This is in agreement with previous investigations on the occurrence of S. vulgaris [ 37 ] and also cyathostomins [ 38 , 39 ] in colic versus control horses. However, there are some publications describing the opposite, such as S. vulgaris -associated colic due to non-strangulating intestinal infarction [ 3 ].…”
Section: Discussionsupporting
confidence: 93%
“…As a matter of fact, recent studies have shown that, in countries with an increased use of selective treatment approaches such as Sweden and Denmark, the S. vulgaris prevalence increased upon the widespread application of this strategy [ 13 , 14 ]. This is in agreement with recent investigations on the occurrence of cyathostomins [ 38 ] or S. vulgaris [ 37 ] in colic versus control horses.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The low anthelmintic treatment intensity reported in this study could be a risk factor for S . vulgaris infection in donkeys as also demonstrated in horses (Nielsen et al ., 2012; Hedberg-Alm et al ., 2020). Considering the high prevalence of S .…”
Section: Discussionmentioning
confidence: 99%
“…was low (1.0%) but in agreement with data reported in donkeys in few studies on the presence of tapeworms in Europe (Matthews & Burden, 2013). In horses, Anoplocephala perfoliata was detected with higher prevalence (Tzelos et al ., 2019; Hedberg-Alm et al ., 2020). This low prevalence could be correlated with the irregular excretion of tapeworm eggs in the faeces (Gasser et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%